Lyapunov-type inequalities for a nonlinear system including operators - Aktaş, Mustafa Fahri; Bingül, Başak Ecem (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.9 We obtain new Lyapunov-type inequalities for a nonlinear system including p-relativistic operator and q-prescribed curvature operator under the Dirichlet or antiperiodic boundary condition.